Helen - Euripides; Allan, William, 1970- (Cambridge : Cambridge University Press, 2008)
This up-to-date edition offers a detailed literary and cultural analysis of Euripides' Helen, a work which arguably embodies the variety and dynamism of fifth-century Athenian tragedy more than any other surviving play. The story of an exemplary wife (not an adulteress) who went to Egypt (not to Troy), Euripides' 'new Helen' skilfully transforms and supplants earlier currents of literature and myth. The Introduction elucidates Euripides' treatment of Helen and sets the play in its wider intellectual context. It also discusses questions of genre and reception, rejecting such descriptions as 'tragicomedy' or 'romantic tragedy', and showing how later artists have responded to Euripides' unorthodox heroine and her phantom double. The Commentary's notes on language and style are intended to make Helen fully accessible to readers of Greek at all levels, while the edition as a whole is designed for use by anyone with an interest in Greek tragedy.
Title from publisher's bibliographic system (viewed on 29 May 2018).
Keywords: elektronické knihy; electronic books; Helen, -- of Troy, Queen of Sparta -- Drama